A Prescription for Note Bloat: An Effective Progress Note Template. Issue 6 (19th January 2018) - Kahn, Daniel; Stewart, Elizabeth; Duncan, Mark; Lee, Edward; Simon, Wendy; Lee, Clement; Friedman, Jodi; Mosher, Hilary; Harris, Katherine; Bell, John; Sharpe, Bradley; El‐Farra, Neveen
Abstract : BACKGROUND: United States hospitals have widely adopted electronic health records (EHRs). Despite the potential for EHRs to increase efficiency, there is concern that documentation quality has suffered. OBJECTIVE: To examine the impact of an educational session bundled with a progress note template on note quality, length, and timeliness. DESIGN: A multicenter, nonrandomized prospective trial. SETTING: Four academic hospitals across the United States. PARTICIPANTS: Intern physicians on inpatient internal medicine rotations at participating hospitals. INTERVENTION: A task force delivered a lecture on current issues with documentation and suggested that interns use a newly designed best practice progress note template when writing daily progress notes. MEASUREMENTS: Note quality was rated using a tool designed by the task force comprising a general impression score, the validated Physician Documentation Quality Instrument, 9‐item version (PDQI‐9), and a competency questionnaire. Reviewers documented number of lines per note and time signed. RESULTS: Two hundred preintervention and 199 postintervention notes were collected. Seventy percent of postintervention notes used the template. Significant improvements were seen in the general impression score, all domains of the PDQI‐9, and multiple competency items, including documentation of only relevant data, discussion of a discharge plan, and being concise while adequately complete. Notes had approximately 25% fewer lines and were signed on average 1.3 hours earlier in the day. CONCLUSIONS: The bundled intervention for progress notes significantly improved the quality, decreased the length, and resulted in earlier note completion across 4 academic medical centers.